2011
DOI: 10.1364/jocn.3.000493
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Comparison of the CMA and ICA for Blind Polarization Demultiplexing

Abstract: Abstract-An algorithm based on independent component analysis for blind polarization demultiplexing in a coherent transmission system is presented. A comparison with the constant modulus algorithm in terms of the convergence properties is performed, and it is found that the suggested algorithm has a significantly faster convergence rate and does not have any singularity problems. We also demonstrate that the algorithm convergence is strongly dependent on the choice of starting condition and show how this can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The convergence rate of the three algorithms can be improved by parallelization [33], where the computations are performed for a number of different initial matrices in parallel and the best candidate is chosen at a later stage.…”
Section: E Convergence Ratementioning
confidence: 99%
“…The convergence rate of the three algorithms can be improved by parallelization [33], where the computations are performed for a number of different initial matrices in parallel and the best candidate is chosen at a later stage.…”
Section: E Convergence Ratementioning
confidence: 99%
“…In this paper we extend the work of [8]- [10] by considering the use of ICA not only for polarization demultiplexing, but also for the equalization of channel polarization impairments induced by PMD and PDL. To achieve that we extended the basic single-tap ICA algorithm of [11] to accommodate multi-tap operation [12], and integrated the simulation of the multi-tap ICA-equipped receiver with a detailed model of the link PMD [13] and PDL [14].…”
Section: Introductionmentioning
confidence: 98%
“…In [8] it has been shown by Zhang et al that ICA solves the converge-to-the-same-source problem of CMA while maintaining similar polarization tracking capabilities. In [9], Xie et al have shown that ICA can be used for blind demultiplexing of 16-QAM polarization multiplexed signals, and in a recent paper by Johannisson et al [10] the use of ICA was proposed for arbitrary constellations with multiple amplitude levels and was shown to significantly outperform CMA in terms of convergence rates.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2008 [28], CMA2-2 and its variants have become the most experimented algorithms for blind polarization demultiplexing [29][30][31][32][33][34][35][36]. In [37], authors have compared CMA2-2 with an independent component analysis (ICA) based algorithm to demultiplex the polarization adaptively. Recently in [38][39][40][41][42][43], authors have used MMA2-2 and its variants as a joint adaptive solution for blind demultiplexing and carrier phase recovery in coherent optical system.…”
Section: Introductionmentioning
confidence: 99%